2014
DOI: 10.3109/10641963.2014.954711
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional activity of kidney genes in hypertensive ISIAH and normotensive WAG rats

Abstract: Transcriptional activity of the kidney genes was compared in hypertensive ISIAH and normotensive WAG rats using the oligonucleotide microarray technique. Most of differentially expressed genes were downregulated in ISIAH kidney both in renal cortex and medulla. According to functional annotation the kidney function in ISIAH rats is based on altered expression of many genes working in stress-related mode. The alterations in gene expression are likely related to both pathophysiological and compensatory mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…In the current study, we found multiple DEGs related to response to different stimuli and to stress. This is well consistent with the previous observation that HPA and sympathoadrenal systems are activated in ISIAH rats [ 11 ] and that the changes in kidney function of 6-month old ISIAH rats are based on altered expression of many genes working in stress-related mode [ 19 ]. The stress response (or stress cascade) is considered as disruptions in homeostasis which result in a series of neural and endocrine adaptations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we found multiple DEGs related to response to different stimuli and to stress. This is well consistent with the previous observation that HPA and sympathoadrenal systems are activated in ISIAH rats [ 11 ] and that the changes in kidney function of 6-month old ISIAH rats are based on altered expression of many genes working in stress-related mode [ 19 ]. The stress response (or stress cascade) is considered as disruptions in homeostasis which result in a series of neural and endocrine adaptations.…”
Section: Discussionsupporting
confidence: 92%
“…So, the decreased expression of Comt in the renal cortex of ISIAH rats may lead to increase in renal dopaminergic effects and sodium excretion, and may be considered as an adaptive mechanism. Earlier, the significantly decreased transcription of Comt was also detected in kidney of 6-month old ISIAH rats [ 19 ].…”
Section: Discussionmentioning
confidence: 92%
“…So, the decreased expression of Comt in the renal medulla of ISIAH rats may lead to increase in renal dopaminergic effects and sodium excretion, and may be considered as an adaptive or protective mechanism for control of hypertension development in ISIAH rats. Earlier, the significantly decreased transcription of Comt was also detected in kidney of 6-month old ISIAH rats [53]. …”
Section: Discussionmentioning
confidence: 92%
“…Comparative analysis of gene expression profiling in kidney of hypertensive ISIAH and normotensive WAG rats revealed 126 differentially expressed genes in renal cortex and 65 differentially expressed genes in renal medulla [ 12 ]. The hierarchical clustering and heatmaps illustrating each individual's expression pattern in genes differentially expressed (p < 0,01) in kidney of hypertensive ISIAH and normotensive WAG rats are shown in Figures 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The functional annotation of the genes differentially expressed in ISIAH and WAG kidney helped to suggest the genetic determinants related to blood pressure control in ISIAH rats. The analysis showed that many genes are working in stress-related mode in hypertensive kidney and the alterations in gene expression are likely related to both pathophysiological and compensatory mechanisms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%